Pulmonary Function of Patients with Juvenile Diabetes Mellitus - Torel Ergtir Ayga; Onarlioglu Turhan; Baskin Esra (Indonesian Pediatric Society, 1996)
In this study, respiratory functions were applied on 20 patients (10 boys and 10 girls) with juvenile diabetes mellitus and 20 healthy subjects (10 boys and 10 girls) followed up for 2.5 (SD 1.2) years on the average. Vital capacity (VC), maximal voluntary ventilation (MW), forced volume in 1 second (FEV1) and mean forced expiraÂtory flow during the middle half of the FVC (FEF 25-75) parameters were evaluated. No significant difference was observed in the ages, heights and weights of diabetic and healthy children. A statistically significant decrease was observed in the VC (1.90, SD 0.13) and FEV1 (1.62, SD 0.54) parameters in diabetic boys and MW (42.10, SD 5.16) and FEV1 (1.55, SD 0.43) parameters of diabetic girls when compared with those of the control group. These results suggested a restrictive process in patients with juvenile diabetes mellitus.